Geografia em Comunidade: social entrepreneurship, university extension and innovative pedagogic initiatives in Diamantina, Minas Gerais state, Brazil (Revista Geografias, 2018)
In the past decade, projects articulating university extension, social entrepreneurship and critical training of teachers in undergraduate courses have brought new perspectives for education and for local development policies. Since 2013, the project Geografia em Comunidade (Geography within Communities), developed in the Cidade Nova neighborhood (Diamantina-MG) by professors and students from UFVJM, has creating a new generation of social entrepreneurs in education, who are focused on school improvement, collaborative learning and local development. This study provides a critical review of the literature on university extension practices and social entrepreneurship in education, exploring possible contributions to collaborative learning in the teacher training process. In addition, this study presents a reflexive analysis on the Geografia em Comunidade project between 2013 and 2017 by taking into account local spatial, demographic and socioeconomic contexts. Project activities are described within a schematic model elaborated by the authors that synthesizes the possibilities of integration among university, school, public power and private sector. The study demonstrates that the Geografia em Comunidade project has an enormous potential for replication by inspiring other projects.